(untitled) (Fiep Bulletin - online, 2013)
The Classical Ballet is a form of academic dance, which by its degree of difficulty, requires a specific physical conditioning. This study sought to verify the sensation perceived by dancers in the body and on his posture during the execution of movements and souplesse Cambra - exercises specific to the ballet, in which the spine is often approached, identifying the most frequent complaints of pain associated with the column and reports to the peculiar context of the movements of classical dance. The study was conducted with eight dancers and four dancers, aged from 13 to 35 years of advanced levels, an academy of ballet in Fortaleza-CE. The results showed that they feel pain or discomfort when performing the exercises without proper attention and consciousness. Amid the complexity and beauty that has classical dance, health should be the priority, so it is suggested that the dancers have access to information about physical conditioning, stretching, posture quality, professional monitoring of Physical Education, with theoretical knowledge in practice and the dance. So studies of dance, and their relationship to health promotion are needed in search of better quality of life of dancers.